2006
DOI: 10.1177/0748233706074173
|View full text |Cite
|
Sign up to set email alerts
|

ATSDR evaluation of the health effects of zinc and relevance to public health

Abstract: As part of its mandate, the Agency for Toxic Substances and Disease Registry (ATSDR) prepares toxicological profiles on hazardous chemicals found at Comprehensive Environmental Response, Compensation, and Liability Act (CERCLA) National Priorities List (NPL) sites, which have the greatest public health impact. These profiles comprehensively summarise toxicological and environmental information. This article constitutes the release of portions of the Toxicological Profile for Zinc. The primary purpose of this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 245 publications
(453 reference statements)
0
14
0
1
Order By: Relevance
“…This element has many regulations on the function of many metalloenzymes. Depressed mental function is one of the problems caused by zinc deficiency [3]. In addition, it was observed that zinc supplementation has been proven to decrease diarrhea morbidity and mortality [4].…”
mentioning
confidence: 99%
“…This element has many regulations on the function of many metalloenzymes. Depressed mental function is one of the problems caused by zinc deficiency [3]. In addition, it was observed that zinc supplementation has been proven to decrease diarrhea morbidity and mortality [4].…”
mentioning
confidence: 99%
“…V is found in different oxidation states, the most common being vanadium pentoxide is known to induce aneugenic events (Zhong et al 1994). Concerning Zn exposure, even if at low concentrations, this PHE acts as a protector of genome stability, at concentrations higher than physiological ones, weak clastogenic effects were reported (Roney et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Compensation and Liability Act (CERCLA). [46], ATSDR and US Department of Human Health Service, published on the toxicological profiles of zinc metabolism including absorption, distribution, metabolism and excretion (ADME).…”
Section: Discussionmentioning
confidence: 99%